Modelling the reality in planning: SPDSS experiences in Malaysia - Abdullah, Alias; Abdullah, Muhammad Faris; Muhammad Nur Azraei, Shahabudin; Richard E, Klosterman (Environmental Management Society Malaysia, 2009)
Spatial Planning and Decision Support System (SPDSS) is a computer system that provides information to help town planners and decision makers to make better informed decisions. Since the mid 1990s, a number of initiatives have been undertaken to explore SPDSS potentials in Malaysian town and country planning field, both theoretically and practically. The public planning agencies have been the main player in exploring SPDSS application in real-life project, while the academics are more content towards investigating potential new areas for SPDSS application in Malaysian planning. Simultaneously, to ensure greater application and appreciation of SPDSS, efforts have also been directed towards introducing SPDSS to wider audience, not just town planners, but also decision makers.